QUALITY OF LIFE OF ADVANCED CERVICAL CANCER PATIENTS WITH PERCUTANEOUS NEPHROSTOMY IN HASAN SADIKIN HOSPITAL BANDUNG FROM 2018-2020 - Wahyudi, Yuvi; Tjahjodjati (Indonesian Urological Association, 2025)
Objective: This study aims to assess the quality of life patients with advanced stage of cervical cancer in RSUP Dr. Hasan Sadikin Bandung from 2018-2020. Material & Methods: This is a retrospective cohort study. The data collected from woman with advanced stages of cervical cancer without history of mental health problems or recurrent cancer, and interviewed using a validated EORT CQLQ-C30 questionnaire to assess their quality of life, and functional status based Karnofsky Performance Score (KPS) and Eastern Cooperative Oncology Group (ECOG) Performance Scale. Scores are calculated into raw score and linear transformation to standardized the range of 1-100. Results: 77 women were included in this study. The average age was 47.98 ± 8.46 years. Cervical cancer predominated by stage IIIa and IV (37,66%) with bilateral nephrostomy (58.44%). This study revealed an average of 63.1 in overall health status, which means there is an improvement over patient’s symptoms resulted from the insertion of nephrostomy, and a poor quality of life with an average score of 48.3 which shows the progression of cervical cancer conditions suffered by patients. Conclusion: The use of nephrostomy in patients with advanced-stage cervical cancer (IIIa, IIIb, and IV) could help alleviate patient’s symptoms, but the progressive condition of cervical cancer has made the patient's quality of life continue to decline. This is shown by the poor quality of life score in the advanced stages of cervical cancer patients, even with nephrostomy insertion. A better understanding of the complexity of the relationship between patient’s quality of life, cervical cancer staging, and the use of nephrostomy is necessary to help cervical cancer patients deciding the best consent before any actions taken. Keywords: EORTC QLQ-C30, cervical cancer, quality of life.